1983
DOI: 10.1139/m83-143
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the most frequent N2-fixing bacteria in a rice rhizosphere

Abstract: Representative N2-fixing bacteria have been isolated from the rhizosphere of rice using the "spermosphere model." They have been characterized using conventional biochemical tests, DNA composition, and DNA–rRNA hybridization studies. In addition to a large number of Enterobacteriaceae, the most commonly encountered isolates belong to the genus Azospirillum and to Pseudomonas paucimobilis, a taxon related to Flavobacterium capsulatum. A nonmotile Azospirillum has been found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
1
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(48 citation statements)
references
References 26 publications
1
45
1
1
Order By: Relevance
“…Rhizobium etli CFN42 was grown in tryptone-yeast extract medium supplemented with 6 mM CaCl 2 (9). For cloning purposes, Escherichia coli strains containing recombinant plasmids were grown in 2YT (yeast extract [5 ]) broth or agar at 37°C with chloramphenicol at 100 g ml Ϫ1 (53).…”
Section: Methodsmentioning
confidence: 99%
“…Rhizobium etli CFN42 was grown in tryptone-yeast extract medium supplemented with 6 mM CaCl 2 (9). For cloning purposes, Escherichia coli strains containing recombinant plasmids were grown in 2YT (yeast extract [5 ]) broth or agar at 37°C with chloramphenicol at 100 g ml Ϫ1 (53).…”
Section: Methodsmentioning
confidence: 99%
“…A. lipoferum 4T retains the ability to efficiently colonize rice roots (2). Like 4V I , A. lipoferum 4T was found to be genetically very close to A. lipoferum 4B (3,8,28), suggesting that A. lipoferum 4T could in fact be a 4V I variant of strain 4B generated within the soil ecosystem.…”
Section: ϫ3mentioning
confidence: 95%
“…The 4V I variant exhibits pleiotropic modifications; it gained assimilation of certain sugars but lost the ability to assimilate other sugars (3), to reduce triphenyl tetrazolium chloride, to bind some dyes, to swim (4), and to reduce nitrous oxide (our unpublished results). A. lipoferum 4T, a nonswimming strain displaying all of the features of the 4V I variant, and strain A. lipoferum 4B have been isolated simultaneously from rice rhizosphere at the same frequency (8). A. lipoferum 4T retains the ability to efficiently colonize rice roots (2).…”
Section: ϫ3mentioning
confidence: 99%
“…In the rice root zone, N 2 fixation is associated with the activity of N 2 -fixing heterotrophic bacteria (4,20). It has been reported that a large percentage of the total aerobic heterotrophic population in the root is diazotrophic (1,10,17). However, studies on the rhizospheric N 2 -fixing microflora have until now suffered from the use of selective media for counts and isolations, because it is widely believed that only a small percentage of natural prokaryotes may actually be culturable (18,19).…”
mentioning
confidence: 99%